Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Cinnamon Coffee And Eatery - Maulida, Noorlaily; Periyadi , Periyadi; Junaidi, Junaidi (STAI Denpasar Bali, 2024)
: The aim of this research is to determine the influence of service quality on customer satisfaction at Cinnamon Coffee and Eatery simultaneously, partially and dominantly . Type of explanatory research (Explanatory Research) with a quantitative approach. Based on the research results, it is known that Tangibles (X 1 ), Reliability (X 2 ), Responsiveness (X 3 ), Assurance (X 4 )and Empathy (X 5 ) simultaneously have a significant effect on customer satisfaction at Cinnamon Coffee and Eatery . Cinnamon Coffee and Eatery can improve the quality of reliability so that it can increase customer satisfaction than before, by providing more responsive and fast service, so that customers don't wait long to enjoy a product.